Level of Teacher Understanding of Simple Technology Early Childhood Education (ECCE) in Kedurang District, South Bengkulu - Sintia Anggraini (CV. Media Inti Teknologi, 2023)
The purpose of this study is to describe the level of teacher understanding of simple technology and make evaluation materials to apply the importance of applying simple technology before learning in Kedurang District, South Bengkulu Regency. The study used a quantitative decryption approach. The population in this study is Early Childhood Education teachers in Kedurang District, South Bengkulu Regency. The sample in this study was a total sample of 52 ECCE teachers using questionnaires to collect data, after the data was collected in analysis using ordinal level category formulas. The results showed that the level of understanding of Early Childhood Education teachers in Kedurang District towards simple early childhood technology was low. The level of teacher understanding of translation, interpretation, and extrapolation of simple learning technologies is low. The suggestion from this study is that it is recommended for ECCE teachers to further improve and understand the importance of simple technology in children, by attending seminars and training related to simple technology.